Self-assessment to subjective creativity and new ideas: determinant within risk taking, autonomy and tradition - Ngọc Trung, Nguyễn; Thị Hoai Le, Nguyễn; Viết Hồi, Trần; Kim, Won Joong (Creativity Studies, 2021)
Individuals’ creativity and new ideas today are not only essential for firms, agencies or organizations but also indispensable even for a nation. This article analyzes impacts of autonomy, risk taking and, especially, factor of tradition on self-assessment to subjective creativity and attitude to new ideas. Specifically, the article empirically analyzes how those factors affect creativity and new ideas and tests whether tradition is more meaningful than others in explaining creativity or new ideas. Most of previous research has theoretically concluded that, because of rigid and unchangeable norms and rules in tradition, individuals are not easy to generate or do new things, especially in Eastern countries. South Korea, with a long tradition within Asian and Confucian values, it is said that these values may limit creativity and new ideas. However, South Korea has achieved satisfactory outcomes in process of creative development, which could positively be affected by its tradition. Using the data from World Values Survey for South Korea at the latest wave 6th, the results show that tradition has a positive impact on subjective creativity beside significantly positive influence of risk taking, which is not considered to be important from cultural perspective.